Long range cooperative interactions regulate the initiation of replication in the Tetrahymena thermophila rDNA minichromosome. - Reischmann, K P (1999)
The Tetrahymena thermophila rDNA exists as a 21 kb palindromic minichromosome with two initiation sites for replication in each half palindrome. These sites localize to the imperfect, repeated 430 bp segments that include the nucleosome-free domains 1 and 2 (D1 and D2). To determine if the D1 and D2 segments act independently or in concert to control initiation, stable DNA transformation assays were performed. Single domain derivatives of the plasmid prD1 failed to support autonomous replication in Tetrahymena. Instead, such constructs propagated exclusively by integration into endogenous rDNA minichromosomes and displayed weak origin activity as detected by 2D gel electrophoresis. D1/D1 and D2/D2 derivatives also transformed Tetrahymena poorly, showing similar replication defects. Hence, the D1 and D2 segments are functionally non-redundant and cooperate rather than compete to control initiation. The observed replication defect was greatly reduced in a plasmid derivative that undergoes palindrome formation in Tetrahymena, suggesting that a compensatory mechanism overcomes this replication block. Finally, using a transient replication assay, we present evidence that phylogenetically-conserved type I elements directly regulate DNA replication. Taken together, our data support a model in which cooperative interactions between dispersed elements coordinately control the initiation of DNA replication.